Geomagnetic Pulsations Driving Geomagnetically Induced Currents - M. J. Heyns; S. I. Lotz; C. T. Gaunt (Space Weather)
Abstract Geomagnetically induced currents (GICs) are driven by the geoelectric field induced by fluctuations of Earth's magnetic field. Drivers of intense GICs are often associated with large impulsive events such as coronal mass ejections. To a lesser extent fluctuations from regular oscillations of the geomagnetic field, or geomagnetic pulsations, have also been identified as possible drivers of GICs. In this work we show that these low‐frequency pulsations are directly observed in measured GIC data from power networks. Due to the low‐pass nature of GICs, Pc5 and lower‐frequency pulsations drive significant GICs for an extended duration even at midlatitudes. Longer‐period Ps6‐type disturbances apparently not typical of midlatitudes are seen with GIC amplitudes comparable to the peak GIC at storm sudden commencement. The quasi‐ac (alternating current) nature of the sustained pulsation driving affects the power system response and cannot be properly modeled using only direct current (dc) models. A further consideration is that the often used dB/dt GIC proxy is biased to the sampling rate of the geomagnetic field measurements used. The dB/dt metric does not adequately characterize GIC activity at frequencies in the low ultralow‐frequency (ULF) range, and a frequency‐weighted proxy akin to geoelectric field should be used instead.